A study of the effect of some antifungals and plant extracts on the growth of some dermatophytes that cause ringworm diseases [Ring worm] (Journal of the College of Basic Education, 2022)
Minimal Inhibititory Concentration (MIC) and Minimal Fungicidal Concentration (MFC) were tested using cultural mixing method for three antifungal :- Fluconazole (FLU) , Itraconazole )ITZ) and Griseoflvin (GRI), against dermatophytes isolates(Trichophyton. mentagrophytes ,Trichophyton verrcossum , Trichophyton rubrum and Trichophyton tonsurans. Results showed that all species of Trichophyton showed sensitivity against (FLU) and the rate of (MIC) for (FLU) , )ITZ) and ( GRI) 5.13 µg /ml , 0.46 µg /ml and 8.35 µg /ml , respectively , while (MFC) 9.20 µg /ml , 0.89 µg /ml and 16.92 µg /ml respectively . Peel extract of Punica granatum and seed extract of Carica papaya were prepared using water and ethanol . The inhibitory effect of extracts against the growth of T. mentagrophytes were depended on extract kind and extract concentration . The peel of Punica granatum alcohol extract showed the highest inhibition activity with a rate of 100% in both concentration (5% and 7.5%) , while the aqueous extract with concentration 7.5% showed the highest inhibition activity with a rate of 100% . The seed of papaya alcohol extract showed the highest inhibition activity with a rate of 100% in both concentration (5% and 7.5%) , whereas the aqueous extract with concentration 7.5% showed the highest inhibition activity with a rate 70.59 % .